THE FORMULA FOR SQUARING A POLYNOMIAL AND ITS POSSIBILITIES APPLICATIONS FOR SOLVING PROBLEMS - Kossanov Б.М; Eraliyev С.; Nurbayeva Д.М; Nurmukhamedova Ж.М (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
When thinking about teaching mathematics in a secondary school, it is important to emphasize that teachers of mathematics should always strive to find new, most beneficial methods for solving problems. Of course, even in identical transformations of polynomials, the character of their search in this field does not change. The article is devoted to one of the actual problems of teaching mathematics in secondary schools – the problem of methods for studying abbreviated multiplication formulas. Abbreviated multiplication formulas are the Foundation of the entire school algebra course. In other words, they can be considered the alphabet of algebra. The article shows a more rational method for deducing the formula for squaring a polynomial , and this formula is considered as an additional formula for reduced multiplication. There are also many examples of using this formula in solving various problems